2017
DOI: 10.7759/cureus.1233
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Syndrome in a Child with Neurofibromatosis Type 1: Magnetic Resonance Imaging as a Tool for Clinical Decision Making

Abstract: Moyamoya syndrome is a rare cerebrovasculopathy of unknown etiology which is associated with multiple risk factors. Moyamoya was first discovered in Japan and is reported to have an increased prevalence in the Japanese population. The term “Moyamoya” translates into “puff of smoke” and is named after the finding of the collateral cerebral vasculature that develops secondary to occlusion of an internal carotid artery at the entrance into the circle of Willis. This collateral vasculature characterizes the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We found 12 (11%) papers describing an association between moyamoya and Neurocutaneous disorders, including one case of tuberous sclerosis [35] and the rest of neurofibromatosis type 1 (NF1) [24][25][26][27][28][29][30][31][32][33][34]. One study found approximately 250 children with NF1 in the literature since 1976 [12], and another NIS study found 51 of 2,247 moyamoya patients with NF between 1988 and 2004 [17].…”
Section: Disease Associationsmentioning
confidence: 99%
“…We found 12 (11%) papers describing an association between moyamoya and Neurocutaneous disorders, including one case of tuberous sclerosis [35] and the rest of neurofibromatosis type 1 (NF1) [24][25][26][27][28][29][30][31][32][33][34]. One study found approximately 250 children with NF1 in the literature since 1976 [12], and another NIS study found 51 of 2,247 moyamoya patients with NF between 1988 and 2004 [17].…”
Section: Disease Associationsmentioning
confidence: 99%
“…It is possible to diagnose with suspected MMD if there is narrowing and/or occlusion of the distal part of both internal carotids or the large arteries of the circle of willis (anterior, middle and posterior cerebral arteries) without excessive collateral vessel networks or unilateral narrowing and/or occlusion of the distal part of an internal carotid artery with an excessive collateral vessel network of vessels distal to the occluded artery [6]. To confirm a diagnosis of MMD, there must be a magnetic resonance angiography or conventional angiography showing narrowing or occlusion of the terminal portion of both internal carotid arteries, and a collateral network of small vessels distal to the occluded arteries unilaterally or bilaterally [6,7].…”
Section: Introductionmentioning
confidence: 99%